An "On‐Demand", Selective Dehydrogenative Borylation or Hydroboration of Terminal Alkynes Using Zn2+‐based Catalyst. Issue 9 (14th March 2022) - Jaiswal, Kuldeep; Groutchik, Kristina; Bawari, Deependra; Dobrovetsky, Roman
Abstract: An air‐stable dicationic Zn 2+ complex (1 ) in a tripod‐type ligand with non‐bound phosphorus base and three pyridinyl "arms" (TPPh) was synthesized. Remarkably, while 2 mol% of 1 at room temperature selectively catalyzed dehydrogenative borylation of terminal alkynes with HBPin, a lower loading of 1 (0.5 mol%) at 90 °C selectively promoted hydroboration reaction of the same alkynes skipping the dehydrogenative borylation step. The mode of action of 1 was proposed based on experimental observations as well as the mechanism of dehydrogenative borylation was studied by DFT computations. Abstract : Alkyne dehydrogenative borylation and hydroboration : A catalytic amount of a dicationic Zn 2+ complex, [TPPh ⋅ Zn] 2+, selectively catalyzed the dehydrogenative borylation of terminal alkynes with HBPin at room temperature while lower [TPPh ⋅ Zn] 2+ loading sborylation step.